Pengaruh Strategi Promosi Terhadap Minat Berkunjung Kembali Wisatawan Di Wisata Mangrove Sreseh (WMS) Spot Desa Marparan, Kecamatan Sreseh, Kabupaten Sampang. - khamilah, faizatul; Andriani, Nurita (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This research aims to examine the influence of Personal Selling and Direct Marketing, either simultaneously or partially, on tourists' revisit interest in visitors to the Sreseh Mangrove Spot tourist attraction in Marparan Village. This research is quantitative research with the variables personal selling, direct marketing and tourist interest in returning to visit. The data analysis technique used is multiple linear regression analysis. The number of samples in this research was 67 people. The sampling method used was purposive sampling with certain criteria. The results of the research show that a) Personal selling has a partially positive and significant effect on tourists' interest in returning to visit Sreseh Mangrove Tourism, b) Direct Marketing has a partially positive and significant effect on tourists' interest in returning to visit Sreseh Mangrove Tourism, c) Personal Selling and Direct Marketing has a positive and significant effect simultaneously on tourists' interest in returning to Sreseh Mangrove Tourism.